Constraints on the off-shell Higgs boson signal strength in the high-mass ZZ and WW final states with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; et al. (The European physical journal. C, Particles and fields, 2015)
Measurements of the ZZ and WW final states in the mass range above the 2mZ and 2mW thresholds provide a unique opportunity to measure the off-shell coupling strength of the Higgs boson. This paper presents constraints on the off-shell Higgs boson event yields normalised to the Standard Model prediction (signal strength) in the ZZ→4ℓ, ZZ→2ℓ2ν and WW→eνμν final states. The result is based on pp collision data collected by the ATLAS experiment at the LHC, corresponding to an integrated luminosity of 20.3 fb−1 at a collision energy of s√=8 TeV. Using the CLs method, the observed 95 % confidence level (CL) upper limit on the off-shell signal strength is in the range 5.1–8.6, with an expected range of 6.7–11.0. In each case the range is determined by varying the unknown gg→ZZ and gg→WW background K-factor from higher-order quantum chromodynamics corrections between half and twice the value of the known signal K-factor. Assuming the relevant Higgs boson couplings are independent of the energy scale of the Higgs boson production, a combination with the on-shell measurements yields an observed (expected) 95 % CL upper limit on ΓH/ΓSMH in the range 4.5–7.5 (6.5–11.2) using the same variations of the background K-factor. Assuming that the unknown gg→VV background K-factor is equal to the signal K-factor, this translates into an observed (expected) 95 % CL upper limit on the Higgs boson total width of 22.7 (33.0) MeV.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, M. Geisler, P. Hanke, J. Jongmanns, E.-E. Kluge, A. Kugel, V. Lang, K. Meier, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, M. Wessels [und 2801 weitere Personen]
Gesehen am 08.07.2021